Catalogue, Thirtieth Bienal de Sao Paulo : The Imminence of Poetics. - Martins, Heitor; Bhabba, Homi K.; Perze-Oramas, Luis; Severo, Andre; Maier, Tobi; Barbieri, Stela; Corullon, Martin; Stolarski, Andre (Fundacao Bienal de Sao Paulo., 2012)
Absalon; Gomes, Alair; Bitar, Alberto; Cesarco, Alejandro; da Cunha, Alexandre; navarro; Moreira, Alexandre; Cortina, Alfredo; Kazma, Ali; Kaprow, Allan; Eriksson, Andreas; Opperman, Ana; Kimura, Yuki; Bing, Xu; Cordeiro, Waldemar; Sipp, Thomas; Borges, Sofia; Hicks, Sheila; Filliou, Robert, Laguna, Lucia; Davey, Moyra; Cais, Nino; Koether, Jutta; Zurier, John
30th Bienal de Sao Paulo, the Imminence of Poetics, Sao Paulo, 7 september - 9 december 2012
boek